Micro-computed tomographic evaluation of canal retreatments performed by undergraduate students using different techniques - Emmanuel João Nogueira Leal Silva; Felipe Gonçalves Belladonna; Marianna Fernandes Carapiá; Brenda Leite Muniz; Mariana Santoro Rocha; Edson Jorge Lima Moreira (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the amount of remaining root canal filling materials after retreatment procedures performed by undergraduate students using manual, rotary, and reciprocating techniques through micro-computed tomographic analysis. The incidence of instrument fracture and the instrumentation time were also evaluated.Materials and MethodsThirty maxillary single rooted teeth were prepared with Reciproc R25 files and filled with gutta-percha and AH Plus sealer by the continuous wave of condensation technique. Then, the specimens were assigned to 3 groups (n = 10), according to the retreatment technique used: manual, rotary, and reciprocating groups, which used K-file, Mtwo retreatment file, and Reciproc file, respectively. Retreatments were performed by undergraduate students. The sample was scanned after root canal filling and retreatment procedures, and the images of the canals were examined to quantify the amount of remaining filling material. The incidence of instrument fracture and the instrumentation time were recorded.ResultsRemaining filling material was observed in all specimens regardless of the technique used. The mean volume of remaining material was significantly lower in the Reciproc group than in the manual K-file and Mtwo retreatment groups (p < 0.05). The time required to achieve a satisfactory removal of canal filling material and refinement was significantly lower in the Mtwo retreatment and Reciproc groups (p < 0.05) when compared to the manual K-file group. No instrument fracture was observed in any of the groups.ConclusionsReciproc was the most effective instrument in the removal of canal fillings after retreatments performed by undergraduate students.